Biotechnological approaches for the integrated management of crop diseases : Professor L.V. Gangawane festschrift volume - Mayee, C.D.; Manoharachary, C.; Tilak, K.V.B.R.; Mukadam, D.S.; Deshpande, Jayashree; Gangawane, L. V.; Mayee, C. D. (Charudatta Digambarrao), 1946- (Delhi : Daya Pub. House, 2004)
Festschrift for Laxman Vithalrao Gangawane, b. 1944, Indian botanist; contributed articles with reference to India.
Includes bibliographical references and index.
Keywords: Plant diseases; Plant biotechnology; Plant parasites -- Integrated control; Agricultural pests -- Integrated control